Citizenship Rights and Human Rights in the Constitution: A Case Study of the Cancellation of Citizenship Status in Indonesia - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Nihayatur Rohmah; Novita Fitriani (Jurnal Restorasi : Hukum dan Politik, 2024)
Sexual harassment is a serious human rights violation with widespread psychological and social impacts on victims. In Indonesia, sexual harassment is classified as a criminal offense and is explicitly regulated in various laws, including the Indonesian Penal Code (KUHP) and Law No. 12 of 2022 on Sexual Violence Crimes (UU TPKS). Positive law provides a clear legal framework to prosecute perpetrators and protect victims' rights. In contrast, from the perspective of the four major Islamic fiqh schools, Hanafi, Maliki, Shafi'i, and Hanbali, sexual harassment is also considered a major sin that violates Sharia law and must be punished strictly, either with hudud or ta'zir penalties. This study aims to conduct a comparative analysis between the positive law approach in Indonesia and the fiqh perspective of the four Islamic schools regarding sexual harassment, as well as to evaluate how these two legal approaches can complement each other to create a more comprehensive and effective protection strategy. The research method used is normative legal research with legislative, case, conceptual, historical, and comparative approaches. The study results indicate that the integration of positive law and fiqh can enhance protection for victims, raise public awareness, and ensure more just law enforcement that aligns with the local socio-cultural context.